Customer relationship marketing get to know your customers and win their loyalty - Stone, Merlin 1948- (Marketing in action series, 2000)
The authors focus on the customer, emphasising the fact that successful marketing relies on both winning and retaining customers. They provide practical advice, detailed case examples, and tips on how a relationship between supplier and customer can best be cemented.